A spatial interpretation of the persistency of China's provincial inequality - Xiaofan Yu (Frankfurt School of Finance & Management, 2011)
China's rapid economic growth in recent decades has not led to balanced income distribution: inter- and intra-provincial income inequality have been increasing and their respective contribution to the total income inequality remains relatively stable. Based on a new set of prefectural database during a relatively longer period from 1994 to 2008 on Chinese economic development, this paper investigates the nexus between the spatial dependence and income inequality in China on a prefectural level. Using the decomposition results of the inequality and spatial dependence of inter- and intra-provincial groups, and also the choropleth maps of clusters in China, this paper reaches the conclusion that clusters of prefectures and provinces with high positive spatial association are persistent over years in China, and the resulting highly correlated income disparity on both inter- and intra-provincial levels might be lasting for a relatively longer period, implying that spatial dependence is a contributing factor to the regional income inequality in a spatial context.
Keywords: C21; O18; O53; R11; R12; 330; Income distribution; Decomposition of income inequality; Theil index; Spatial econometrics; Cluster; China